The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1074/jbc.272.3.1811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hydrophobic Exosite on Tissue Type Plasminogen Activator That Modulates Specificity for Plasminogen

Abstract: A wide variety of important biological processes, including both the formation and dissolution of blood clots, depend on specific cleavage of individual target proteins by serine proteases. For example, tissue type plasminogen activator (t-PA), a trypsin-like enzyme that catalyzes the rate-limiting step of the endogenous fibrinolytic cascade, has only one known substrate in vivo, a single peptide bond (Arg 561 -Val 562 ) in the proenzyme plasminogen. We have previously suggested that the specificity of t-PA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
(28 reference statements)
2
22
0
Order By: Relevance
“…Measurement of Second Order Rate Constants for Inhibition by PAI-1-Second order rate constants (k i ) for the inhibition of wild type and mutated t-PA were measured under pseudo-first order conditions as described previously (32)(33)(34)(35)(36). Inhibitor was present in at least a 20-fold molar excess over enzyme.…”
Section: Conversion Of Single-chain T-pa Preparations Into Two-chain mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of Second Order Rate Constants for Inhibition by PAI-1-Second order rate constants (k i ) for the inhibition of wild type and mutated t-PA were measured under pseudo-first order conditions as described previously (32)(33)(34)(35)(36). Inhibitor was present in at least a 20-fold molar excess over enzyme.…”
Section: Conversion Of Single-chain T-pa Preparations Into Two-chain mentioning
confidence: 99%
“…Kinetic Analysis of Plasminogen Activation Using Indirect Chromogenic Assays-Indirect chromogenic assays of t-PA utilized the substrates Lys-plasminogen (American Diagnostica) and Spectrozyme PL (American Diagnostica) and were performed as described previously (32,33). Assays were performed both in the presence and absence of the co-factor DESAFIB (American Diagnostica).…”
Section: Conversion Of Single-chain T-pa Preparations Into Two-chain mentioning
confidence: 99%
“…6), the absence of the Cys558 Cys566 bond in plasmin appears also to result in a distinct effect on the degragen activation loop. Studies with tPA variants in which the plasminogen interaction site was modified [23] confirm this assump-dation pattern during more advanced stages of fibrin clot dissolution. These stages are characterised by dissociation of fibres tion, which was further substantiated by the results obtained with our [Ser558, Ser566]Lys78-plasminogen variant.…”
mentioning
confidence: 62%
“…A recent study of substitution of these amino acid leads to an increased activity with respect to cleavage of the AC domain in fibrin(ogen). Since [23] has identified a hydrophobic exosite (residues 420Ϫ423) on the edge of the active site of tPA which, together with the a fast initial plasmin degradation is supposed to result in early appearance of C-terminal lysine residues and an increased bindprimary site, is involved in the interaction with plasminogen. Also, the isolated protease domain of uPA is as active as full-ing of plasminogen to fibrin, this might also explain the increased tPA activity observed with the [Ser558, Ser566]Lys78-length uPA in the absence of stimulator [24].…”
mentioning
confidence: 99%
“…However, recent demonstrations that, compared with wild type t-PA, PAI-1-resistant variants possess enhanced potency toward platelet-rich thrombi but normal potency toward platelet-poor clots, both in vitro and in vivo, strongly suggests an important role for platelet derived PAI-1 during thrombolytic therapy (15,38,39). We have previously suggested that the recruitment of residues in surface loops mapping near the active site of an enzyme to form specific enzyme-inhibitor and/or enzyme-substrate interactions was likely to be an important and recurring theme during the evolution of enzyme specificity (13,21,22,40). The properties of variants of t-PA carrying mutations in the 296 -304 region clearly demonstrate that this mechanism played an essential role during the co-evolution of specificity between t-PA and PAI-1, individual members of two very large and medically relevant gene families.…”
Section: Pai-1-resistant Variants Of T-pamentioning
confidence: 99%